White-collar crimes: Execution of sentences - García, María Agustina; Chabeuf, Tiago Oscar; Bur Ahumada, Pablo Jesús; Alú, Nelson; Acosta, Juan Ignacio; Degano, Juan Martin (Scientific journal of social studies, 2024)
White-collar crimes, characterized by their commission by individuals of high social and economic status, represent a significant problem in modern justice. Unlike conventional crimes, white-collar crimes broadly impact the social and economic structure, involving not only isolated individuals but society as a whole. This study employs a qualitative-descriptive approach to examine the incidence, characteristics, and repercussions of these crimes, using recent scientific articles from Latin American countries and Spain as primary sources. Key terms include "media," "offender profile," and "sociological theories," and the analysis is enriched with contributions from classic theorists such as Becker, Foucault, and Zaffaroni. Additionally, high-profile cases like the Once tragedy in Argentina are examined, which illustrate the complexity of effectively attributing and sanctioning these criminal behaviors. The findings indicate that there is a great difficulty in establishing a clear link between the criminal action and its consequences, which, coupled with the media representation that often minimizes these acts, results in a low frequency of convictions. The study concludes that the lack of recognition of the severity of these crimes and their differential treatment due to the influence and power of the offenders perpetuates disparities in the application of justice, underscoring the need for reforms in the perception and legal approaches toward white-collar crimes.